PUASA BERGIZI DI TENGAH PANDEMI - Palupi, Khairizka Citra; Laili, Aditya Fatkhi; Sabrina, Nindy (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
The ritual of fasting by refraining from food and drink has been a Muslim tradition for thousands of years. Some studies say that Ramadan fasting can improve immune system. This Ramadan fasting moment in 2020 is unique and different from previous years because the world is being hit by the Covid-19 pandemic. The exact relationship of Ramadan and Covid-19 is unknown. So far there has limited information about fasting and Covid-19 in the Esa Unggul University Therefore, we endeavour to provide an information approach based on existing references to improve the understanding of the Esa Unggul campus community regarding nutritious fasting during the Covid-19 pandemic. This community service preparation was carried out in April 2020 which included making online invitations and educational material. Educational material consists of introduction to Ramadan fasting, introduction of Covid-19 and ways of prevention, the role of the immune system against Covid-19, the relationship of the immune system and digestive system, metabolism during fasting, the benefits of physical and mental fasting, optimization of Ramadan fasting, principles and conditions diet, and sample menus delivered in the form of online seminars via zoom. The activity flow is divided into two, namely all participants are given education and afterwards participants are given closed questions related to the understanding of the material presented. The location of the study was conducted online at each place. The community service program was held on Tuesday, May 5, 2020 from 13.00-15.00. Although the effect of fasting on Covid-19 is still unknown, fasting is known to be able to improve physical and mental health. Appreciate your hunger during fasting with food consumption from 5 food groupsÃ‚Â Keywords: pandemic, fasting,nutrition